Leadership and teamwork in a new school : developing a professional learning community - Birna María Svanbjörnsdóttir 1964- (2015)
This research project involves the collaboration of a critical friend and two school leaders in one new compulsory school in an urban area in Iceland. The main research questions were: a) What does leadership for learning mean in the development of practice of one new school? and b) What supports and encourages leadership for learning? The planning for the school began in 2006 and the school itself started in August 2009, at the same time as the research, which ended in December 2012. Prior to the research, the school had decided to use the tool ‘Positive discipline’. Leaders had divided the staff into teaching teams involving teachers and teacher aides. Students would work in learning areas under the supervision of a teaching team. I worked with the two school leaders, provided guidance and evaluated process and practice. As leadership seems to be a strong driver for school improvement I thought it necessary to understand what it involves. I strived to understand concepts such as educational leadership and a professional learning community (PLC), and what they meant for learning in the school. I used action research as a method and my collaboration with the leaders was guided by developing techniques and paths necessary for improving learning. It was also guided by an awareness of the overall importance of supporting leadership in new situations. Evaluation research was used in order for us to follow developments. The phases of the research have been described and discussed in four papers. The main goal with the first paper was to understand and elicit the attitude of the principal towards the leadership role, the issues which needed to be addressed and what was uppermost in his mind when he recruited teachers and a department head to work in the new school. The main focus in the paper was on how the principal interpreted his own role. This was complemented by the views of five teachers and the department head, and information from school visits and interviews. Practical and professional groundwork for the new ...